Federal Income Taxes in the United States - Tax Design and Fiscal Efficiency - Hybka , Małgorzata Magdalena (Studia Oeconomica Posnaniensia, 2016)
Irrespective of the country income tax constitutes one of the most important public revenue sources. In the OECD member states the share of taxes on income, profits and capital gains in the GDP equalled 11,4% in 2012 and varied from 5,2%, Slovakia and Mexico, to 29,2% Denmark [ OECD Revenue Statistics2015]. There are many countries where income taxes are not only imposed by central government but also by sub-central government levels. In the United States income taxes are collected by Federal , State and certain local authorities. The main aim of this article is to pre-sent federal income tax and federal corporate tax design in that country. Moreover it evaluates the role played by these taxes in the American tax system.